Envirotyping helps in better understanding the root cause of success and limitations of rainfed production systems - Sawargaonkar, Gajanan L.; Davala, Moses Shyam; Rakesh, S.; Kamdi, Prasad J.; Khopade, Rohan Y.; Nune, Rajesh; Pasumarthi, Rajesh; Choudhari, Pushpajeet; Datta, Aviraj; Akuraju, Venkata Radha; Dixit, Sreenath; Singh, Ramesh; et al. (Frontiers in Environmental Science, 2024)
The current diagnostic agronomy study of the Bankura region of West Bengal, India examined the variations in crop yields through a socio-ecological analysis of multiple production system components. Root cause analysis for low system productivity was employed in the study to delve into variables that affect the performance of the envirotypes. Mother Earth, Man, Machine, Management, and Materials (5Ms concept) were the five indicators under which the variables were grouped. Findings demonstrated the fragility of the region's soils due to its undulating terrain, unpredictable rainfall patterns, and frequent drought scenarios. The LULC's NDVI showed that the agriculture area is about 60% and 43% of the total geographical area in the Hirbandh and Ranibandh blocks, respectively. Soils are acidic, diagnosed with deficiency of both macro and micronutrients (phosphorous, sulfur, and boron), poor water holding capacity (35 mm-55 mm for a 50 cm depth of soil), high sand content (43.04% to 82.32%), low organic carbon (0.17% to 1.01 %), and low bacterial population. These factors are the root cause for low cropping intensity (106%) and low paddy productivity (3021 kg/ha). Overall, study contributes to scaling-up of sustainable landscape management practices that could ensure higher cropping intensity and system productivity in the similar agro-ecologies with the limited evidence.